The educated underdog becomes the ultimate superstar - Per Hjertstrand; Pehr-Johan Norbäck; Lars Persson (Research Institute of Industrial Economics (IFN), 2017)
We find an inverted relation between a player's birthday and the likelihood of receiving the Ballon d'Or (awarded to the best football player in the world). We develop a multi-period skill formation model with selection into elite education. We show that those born late (underdogs) need to work harder to be selected for elite educational programs. However, those born too late will not make the cut-off. Those born late - but not too late - will thus end up with the highest skill levels as adults (educated underdogs). We use detailed data on the performance of elite Swedish football players to illustrate our model. These data provide strong support for the predictions of the model.
Keywords: D10; I20; J70; M50; Z20; 330; Superstar; Skill formation; Expertise; Relative age effect; Football; Elite education